ISOLASI DAN IDENTIFIKASI ANTIOKSIDAN JAMUR ENDOFIT UMBI TALAS (Colocasia esculenta (L.) Schott) MENGGUNAKAN PEREAKSI SEMPROT DPPH SECARA BIOAUTOGRAFI - Hidayah Syaro Abesah, Nur; mahfur, mahfur (Jurnal Insan Farmasi Indonesia, 2024)
The development of exploration of bioactive compounds by utilizing plant endophytic fungi is a solution to prevent ecological damage due to plant exploitation due to the production of endophytic fungi without large biomass and in a relatively short time. Therefore, this study aims to isolate endophytic fungi of taro tubers (Colocasia esculenta (L.) Schott) and identify the presence of antioxidant activity produced by endophytic fungi of taro tubers by bioautography method. The taro tuber endophytic fungus extract was obtained through the stages of isolation, purification, fermentation, and extraction with ethyl acetate solvent. Antioxidant testing was carried out by TLC-bioautography method using DPPH spray reagent that has been eluted with n-hexan:methanol (1:5) eluent. The results of the isolation of endophytic fungi of taro tubers obtained three fungal isolates coded HJ, HT, and PT. The results of the antioxidant test showed positive results marked by a yellow color change on a purple background after spraying DPPH, where isolates HJ and HT gave a reaction to the spot with Rf values of 0.87 and isolate PT gave a reaction to the spot with an Rf value of 0.90.